Archiving the Virtual: Library Science and the Digital Preservation of Video Game Clones - Priyadarshini, Priyanka; Mishra, Debashrita; Patnaik, Daisy Irani; Chaudhuri, Sudeshna Datta (Indian Journal of Information Sources and Services, 2025)
Libraries, archives and gaming communities should work together for better digital preservation. As video games, their clones and their avatars merge into the mainstream, it’s a problem for libraries and archivists. Preservation is access; it’s also history and technology. This paper will explain how video game clones and avatars are preserved through library science by understanding the logic of what modern librarians do to archive the issues and solutions. Through qualitative methods, including institutional case studies and community-based preservation initiatives, this research will tackle the biggest technical, legal and ethical digital archiving issues. There are still gaps to be highlighted, such as AI-based preservation methods, standardised digital archiving protocols, and blockchain authentication. The problem is that these are basic in the modern digital world and paired with legal, technological, preservation and traditional archiving issues. The research concludes that librarians are the primary custodians of digital heritage, and we need more research and new laws to be able to save that heritage.